2022
DOI: 10.1002/hbm.25987
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography can reveal deep brain network activities linked to memory processes

Abstract: Recording from deep neural structures such as hippocampus noninvasively and yet with high temporal resolution remains a major challenge for human neuroscience. Although it has been proposed that deep neuronal activity might be recordable during cognitive tasks using magnetoencephalography (MEG), this remains to be demonstrated as the contribution of deep structures to MEG recordings may be too small to be detected or might be eclipsed by the activity of large‐scale neocortical networks. In the present study, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 116 publications
3
4
0
Order By: Relevance
“…4 e ). A similar facilitation pattern was found in MEG during the same task ( López-Madrona et al, 2022 ). In that work, the combined activity of the hippocampus and the rhinal cortex presented earlier latencies for old items, although the onset time of the differential activity was not measured.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…4 e ). A similar facilitation pattern was found in MEG during the same task ( López-Madrona et al, 2022 ). In that work, the combined activity of the hippocampus and the rhinal cortex presented earlier latencies for old items, although the onset time of the differential activity was not measured.…”
Section: Discussionsupporting
confidence: 80%
“…This result has suggested that the hippocampus is mainly involved in a slower process that retrieves complementary information ( Despouy et al, 2020a ), although early activations have also been identified for specific source memory effects ( Staresina et al, 2012 ). A similar result was found in a recent magnetoencephalography (MEG) study, with higher amplitudes for recognition memory at ∼500 ms ( López-Madrona et al, 2022 ). Interestingly, the responses to old and new elements were different not only in amplitude but also in delay, with faster activations for recognized items.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…This neuronal facilitation would be reflected in the ERP, with earlier latencies for old items (Figure 3e). Interestingly, we identified a similar facilitation pattern in magnetoencephalography (MEG) during the same task (López-Madrona et al, 2022). In that work, the combined activity of the hippocampus and the rhinal cortex presented earlier latencies for old items.…”
Section: Early Memory Recognition System Of the Hippocampussupporting
confidence: 72%
“…We used the same experimental visual memory paradigm as in López-Madrona et al ( 2022 ). In summary, we used 168 images from the database of Duñabeitia et al ( 2018 ) that were organized in blocks of 12 or 24 images, presented on a computer screen.…”
Section: Methodsmentioning
confidence: 99%